2019
DOI: 10.3233/jpd-191576
|View full text |Cite
|
Sign up to set email alerts
|

Extended Treatment with Glial Cell Line-Derived Neurotrophic Factor in Parkinson’s Disease

Abstract: Background: Intraputamenal glial cell line-derived neurotrophic factor (GDNF), administered every 4 weeks to patients with moderately advanced Parkinson's disease, did not show significant clinical improvements against placebo at 40 weeks, although it significantly increased [ 18 F]DOPA uptake throughout the entire putamen. Objective: This open-label extension study explored the effects of continued (prior GDNF patients) or new (prior placebo patients) exposure to GDNF for another 40 weeks. Methods: Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 27 publications
3
100
1
Order By: Relevance
“…Our study used an AAV2 vector encoding GDNF. Whone and colleagues recently reported a blinded clinical study of CED delivering intraputaminal GDNF protein versus placebo in PD patients . GDNF infusion was safe and well tolerated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study used an AAV2 vector encoding GDNF. Whone and colleagues recently reported a blinded clinical study of CED delivering intraputaminal GDNF protein versus placebo in PD patients . GDNF infusion was safe and well tolerated.…”
Section: Discussionsupporting
confidence: 90%
“…Whone and colleagues recently reported a blinded clinical study of CED delivering intraputaminal GDNF protein versus placebo in PD patients. 24,25 GDNF infusion was safe and well tolerated. Furthermore, the group receiving GDNF had increased putaminal [ 18 F]FDOPA uptake on PET, as in our study, suggesting neurotrophic effect on putaminal DA neurons.…”
Section: Discussionmentioning
confidence: 88%
“…22 1 years due to inconclusive results of clinical trials with GDNF (Paul and Sullivan, 2019) and preclinical and 2 patient data suggesting the loss of RET receptor in later stages of PD (Decressac et al, 2012;Decressac 3 et al, 2013;Decressac et al, 2011). However, as discussed above, this might not be true for all 4 population of patients, especially those at earlier stages of the disease, and recent clinical trials for 5 GDNF, while not meeting clinical endpoints, demonstrated feasibility of safe, long term GDNF 6 administration (Whone et al, 2019a;Whone et al, 2019b). Importantly, discussing the modest efficacy 7 of GDNF in the latest clinical studies, the authors suggested future modifications of GDNF trials to 8 increase GDNF dosing or include patients at early stages of PD, what is strongly supported by our data.…”
Section: [Main Text]mentioning
confidence: 99%
“…Only 11 of 29 published phase II studies included at least one biomarker measurement in their protocol. These included 11 studies with brain imaging assessments [24,[58][59][60][61][62][63][64], one assessment of 8-hydroxy-2' -deoxyguanosine measurement in plasma and one in urine [65], as well as two studies with cerebrospinal fluid (CSF) analysis of protein aggregation [66,67]. Progress on the usefulness of imaging techniques and fluid or tissue biomarkers has been reviewed extensively by others [56,57,68].…”
Section: Biomarkersmentioning
confidence: 99%